Applicability of the International Affective Picture System in Chinese older adults: A validation study. Issue 2 (3rd June 2016) - Gong, Xianmin; Wang, Dahua
Abstract: The International Affective Picture System (IAPS) is a standardized tool widely used to induce emotions in psychological studies. The present study examined the reliability and validity of the IAPS in Chinese older adults. A sample consisting of 126 Chinese older adults (86 females; aged 67.3 ± 4.96 years; 13.2 ± 2.75 years of education) was recruited to rate valence and arousal for 942 IAPS pictures. The results showed a satisfactory reliability and validity of the IAPS among these participants. The reliability was supported by high internal consistency and low inter‐individual variance of participants' ratings; the validity was supported by high similarities (in rating scores and in the distribution of the pictures in the valence–arousal affective space) and small differences (in mean ratings) between Chinese and German older adults. In conclusion, the study adds supportive evidence to the cross‐cultural validity of the IAPS in older adults, and provides a set of normative emotional ratings that could be adopted as a criterion in the selection of emotional pictures in future studies engaging Chinese older adults. Comparison of the IAPS ratings across cultures and ages is also discussed.